Effect of Body Position on Limb Lead Electrocardiographic Findings in Sedated Cynomolgus Macaques (Macaca fascicularis) - Taylor, Katrina (American Association for Laboratory Animal Science, 2010)
Electrocardiograms (ECGs) often are collected from sedated cynomolgus macaques (Macaca fascicularis) in drug safety studies to support investigational new drug applications. ECGs are evaluated either manually or electronically, and the quality of the ECG tracing can affect the quality of that evaluation. The body position of the subject sometimes is manipulated to eliminate noise or clarify ECG complex morphology, and typically multiple technicians collect ECG data over time. Both factors—body position and multiple technicians—could affect ECG quality. This study was designed to determine whether body position or multiple technicians affects heart rate, mean electrical axis, or ECG parameters (RR interval, P wave duration, PR interval, QRS duration, QT interval (uncorrected and rate-corrected by using the Bazett [QTcb] and Fridericia [QTcf] formulas), P wave amplitude, R wave amplitude, T wave height, T wave height negative, and ST segment elevation). The results reveal minimal (coefficient of variation [CV] less than 10%) within-animal variation between body positions (ventral, dorsal, right or left lateral), with the exception of P wave amplitude (17.5%), R wave amplitude (23.7%), and ST segment elevation (43%). Minimal variation in ECG parameters (no more than 7%) was detected between technicians, across animals, and across body positions. These findings suggest that neither a change in body position to increase the quality of an ECG tracing nor the use of multiple technicians significantly affect the evaluation of quantitative ECG parameters, especially QTcb (0.1% CV) and QTcf (1.3% CV).